A physician survey of perioperative neuraxial anesthesia management in patients on a direct oral anticoagulant. Issue 1 (16th December 2020) - Douketis, James D.; Syed, Summer; Li, Na; Narouze, Samer; Radwi, Mansoor; Duncan, Joanne; Schulman, Sam; Spyropoulos, Alex C.
Abstract: Background: The perioperative management of patients taking a direct oral anticoagulant (DOAC) who require a high‐bleed‐risk surgery and/or neuraxial anesthesia is uncertain. We surveyed clinician practices relating to DOAC interruption and related perioperative management in patients having high‐bleed‐risk surgery with neuraxial anesthesia, and assess the suitability of a randomized trial of different perioperative DOAC management strategies. Methods: We surveyed members of the American Society of Regional Anesthesia and Pain Medicine, the Canadian Anesthesia Society and Thrombosis Canada. We developed four clinical scenarios involving DOAC‐treated patients who required anticoagulant interruption for elective high‐bleed‐risk surgery. In three scenarios, patients were to receive neuraxial anesthesia, and in one scenario they were to receive general anesthesia. We also asked about the merit of a randomized trial to compare a 2‐day versus longer (3‐ to 5‐day) duration of DOAC interruption. Results: There were 399 survey respondents of whom 356 (89%) were anesthetists and 43 (11%) were medical specialists. The responses indicate uncertainty about the DOAC interruption interval for high‐bleed‐risk surgery and/or neuraxial anesthesia; anesthetists favor 3‐ to 5‐day interruption whereas medical specialists favor 2‐day interruption. Anesthetists were unwilling to proceed with neuraxial anesthesia in patients with a 2‐day DOAC interruption interval, preferring to cancel the surgery or switch to general anesthesia. There is general agreement on the need for a randomized trial in this field to compare a 2‐day and a 3‐ to 5‐day DOAC interruption management strategy. Conclusions: There is variability in practices relating to the perioperative management of DOAC‐treated patients who require a high‐bleed‐risk surgery with neuraxial anesthesia; this variability relates to the duration of DOAC interruption in such patients.